2017
DOI: 10.1016/j.jtrangeo.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The capability of Motorways of the Sea of being competitive against road transport. The case of the Italian mainland and Sicily

Abstract: The paper deals with a quantitative analysis on the competitiveness of intermodal transport, based on Motorways of the Sea (MoS), in comparison with all-road transport. This analysis is applied to MoS routes connecting the Italian mainland with Sicily. The study involves: a detailed intermodal network model which compares monetary costs and travel times from all relevant origins in the mainland to all relevant destinations in Sicily; and a survey carried out at some representative trucking firms operating to /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
(16 reference statements)
0
18
0
Order By: Relevance
“…The geo-spatial data of the Mediterranean ferry network, which connects the insular maritime nodes identified in this study and is provided by the European Atlas of the Seas (Figure 9), supports our findings that satisfactory levels of insular regional accessibility exist. More detailed individual studies on the level of connectivity have been carried out for the Greek [40], Croatian [39], and Italian (only Sicily) [72] insular regions in terms of the number of ferry operators, ship calls, voyage times, distances, seasonality, and fares. On such study, carried out by Stupalo et al [39], identified 94 Croatian passenger ports from the islands (73 ports) and mainland (21 ports) and suggested a satisfactory level for their port infrastructure and hinterland accessibility, as most of the island ports are located close to the city centers.…”
Section: Discussionmentioning
confidence: 99%
“…The geo-spatial data of the Mediterranean ferry network, which connects the insular maritime nodes identified in this study and is provided by the European Atlas of the Seas (Figure 9), supports our findings that satisfactory levels of insular regional accessibility exist. More detailed individual studies on the level of connectivity have been carried out for the Greek [40], Croatian [39], and Italian (only Sicily) [72] insular regions in terms of the number of ferry operators, ship calls, voyage times, distances, seasonality, and fares. On such study, carried out by Stupalo et al [39], identified 94 Croatian passenger ports from the islands (73 ports) and mainland (21 ports) and suggested a satisfactory level for their port infrastructure and hinterland accessibility, as most of the island ports are located close to the city centers.…”
Section: Discussionmentioning
confidence: 99%
“…Trieste and Venice. An essential factor of MoS is the reliability; furthermore, the interviews with trucking firms, reported in Lupi et al [11], show that a relevant modal split increase could be achieved by a reduction of MoS ticket prices.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the next popular SSS research area is on the attractiveness and competitiveness of SSS in a multimodal transport chain ( [39], [131], [68], [35], [71], [114], [77], [66], [120], [34], [27], [37], [42], [87], [78], [20], [62], [95], [19], [103], [8], [21], and [9]). This is followed by research on policy, subsidization, funding and government assistance in SSS and multimodal transportation network as the third most popular area ( [132], [44], [59], [60], [82], [114], [112], [12], [51], [81], and [92]).…”
Section: Research Area In Sssmentioning
confidence: 99%
“…This study concludes that SSS in North Europe tends to divide into two different ways, participating in competition as a logistics provider, or strengthening their own position as a pure carrier. With the same approach, [68] investigate the analysis of SSS container routes in the Black Sea and the Mediterranean. Their study revealed that the Italian foreign trade is becoming more oriented to high value goods.…”
Section: Econometric Analysis Cost Benefits Analysis (Cba) Economicmentioning
confidence: 99%